Mental health outcomes in dementia caregivers: a systematic review of yoga-based interventions - Paula Pillar Pinto; Andrea Camaz Deslandes; Helena Moraes (Dementia & Neuropsychologia)
ABSTRACT Mind-body interventions have been explored to enhance the psychological well-being of dementia caregivers; however, the specific effects of yoga practice remain underexamined. Objective: The aim of this study was to investigate the benefits of yoga on quality of life (QoL), life satisfaction, psychological well-being, attention, self-compassion, perceived stress, anxiety, depression, and caregiver burden for dementia caregivers. Methods: A comprehensive search was conducted on September 11, 2024, in databases including SciELO, PubMed, BVSalud, Web of Science, Embase, and PsycINFO, focusing on the effects of yoga for informal dementia caregivers compared to passive or active control groups through randomized and non-randomized trials. An initial review reduced 284 to 180 unique records; 172 studies were excluded, leaving 8 that met the inclusion criteria. Two authors independently selected and extracted data using a data extraction sheet based on the Cochrane Consumers and Communication Review Group. The Cochrane Risk of Bias tools (ROB2 and ROBINS-I) were employed to evaluate bias risk. Results: The review included three randomized and five non-randomized studies with a total of 161 participants, predominantly female (wives and daughters), with ages ranging from 39 to 76 years. Four studies utilized hatha yoga, while four employed non-traditional yoga. Significant improvements were observed in QoL, depression, stress, anxiety, and self-compassion, but not in caregiver burden. Furthermore, positive effects were more pronounced in face-to-face or online interventions than in recorded videos. On average, studies exhibited a moderate risk of bias. Conclusion: Yoga practice can serve as an effective intervention for enhancing the psychological aspects of dementia caregivers.